CHARACTERISTIC AND VARIATION OF Acacia mangium Willd. WOOD PHYSICAL PROPERTIES IN MANY PLANTATION SPACINGS AND AXIAL-RADIAL POSITION - Siarudin Mohamad; Sri Nugroho Marsoem (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
This study aimed to identity characteristic and variation of A. Mangium wood physical properties in different planting spacings and axial-radial position. Materials used were 8 years old Amangium wood from Subanjeriji, Palembang, South Sumatera with three spacings: 2 m x 3 m, 2 m x 4 m and 3 m x 3 m. Three sample trees in diameter of 21 cm from each planting spacing were taken by randomly. Specimens in each tree were taken in 3 axial position (bottom, middle and top of trunk), and 3 radial position (near pith, middle and near bark). Parameters measured were wood density, fresh moisture content (FMC), equilibrium moisture content (EMC), total tangential shrinkage (TS), radial shrinkage (RS), longitudinal shrinkage (LS) and T/R ratio (T/R). The result showed that total averages of wood density, FMC, TS, RS, LS, and T/R were 0,45 gr/cm3; 118,40%; 7,63%; 3,53%; 0,71% and 2,23% respectively. Differences on wood physical properties of three spacing were found at FMC, TS and LS; while other properties were relatively not different. Based on the density, FMC and dimension change A. Mangium wood grown in 2 m x 4 m plantation spacing showed the best performance, that followed by 3 m x 3 m and 2 m x 3 m. Based on axial orientation, wood density tend to increase from bottom to upper stem, FMC, EMC, and TS, while other properties were not different. Based on radial orientation, the wood density and TS tend to increase from near the pith to near the bark, while FMC and LS have reversed pattern.